2023
DOI: 10.14202/vetworld.2023.2210-2216
|View full text |Cite
|
Sign up to set email alerts
|

First report of phenotypic and genotypic (blaOXA-61) beta-lactam resistance in Campylobacter jejuni from broilers in Indonesia

Sheila Marty Yanestria,
Mustofa Helmi Effendi,
Wiwiek Tyasningsih
et al.

Abstract: Background and Aim: Campylobacter is a zoonotic bacterium that is a major source of foodborne diseases. In humans, most cases of campylobacteriosis are caused by Campylobacter jejuni. Poultry is the main reservoir of Campylobacter for humans, because Campylobacter is part of the normal flora of the digestive tract of poultry. Antimicrobial resistance to several antibiotics in Campylobacter isolated from humans and food animals has increased rapidly. Beta-lactam is an antibiotic with a high prevalence of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Premarathne et al (2017) also reported very high resistance of Campylobacter to tetracycline (76.9%) and ampicillin (69.2%); many isolates were relatively susceptible to chloramphenicol as resistance recorded was as low as 7.6%. Yanestria et al (2023) reported the blaOxa-61 gene on Campylobacter jejuni detected in all 23 C. jejuni isolates from broilers in Indonesia, and also a total of 31 Campylobacter jejuni isolates were tested using PCR to detect the gyrA gene encoding fluorquinolone resistance and all (100%) detected the gyrA gene (Yanestria et al 2024).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Premarathne et al (2017) also reported very high resistance of Campylobacter to tetracycline (76.9%) and ampicillin (69.2%); many isolates were relatively susceptible to chloramphenicol as resistance recorded was as low as 7.6%. Yanestria et al (2023) reported the blaOxa-61 gene on Campylobacter jejuni detected in all 23 C. jejuni isolates from broilers in Indonesia, and also a total of 31 Campylobacter jejuni isolates were tested using PCR to detect the gyrA gene encoding fluorquinolone resistance and all (100%) detected the gyrA gene (Yanestria et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…In the developing world, water and milk remain the predominant means of transmission of campylobacteriosis. Therefore, it is clear that reducing Campylobacter in water and foods is a desirable target for maintaining the safety of essential resources (Rukambile et al 2019;Yanestria et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation